Pemanfaatan Abu Terbang (FLY ASH ) sebagai Bahan Penyerap (Adsorbent ) Amonia di Limbah Cair PT. Pupuk Sriwidjaja Palembang - Albari, Mauris; Hasan, Abu; Mustain, Mustain (Universitas Pahlawan Tuanku Tambusai, 2025)
Ammonia is an inorganic compound that is widely used as a basic raw material for fertilizers, if the ammonia level exceeds the quality standard limit, it can cause irritation to the respiratory tract. In addition, if exposed to the environment, it can cause damage. The purpose of this study is to determine the Utilization of Fly Ash as an Ammonia Adsorbent in PT. Sriwidjaja Palembang Fertilizer. This research method is by conducting field observations. Field observation by directly observing the object being studied. The results of this study were obtained from the analysis that fly ash can reduce ammonia concentration by 59.46% from a concentration of 477.448 mg/L to 193.56 mg/L with a contact time of 60 minutes and an activator condensation of 0.5N